On case loss and svarabhakti vowels: the sociolinguistic typology and geolinguistics of simplification in North Germanic. Issue 1 (1st August 2019) - Blaxter, Tam T.; Trudgill, Peter
Abstract: Work in sociolinguistic typology and creole studies has established the theory that intensive language contact involving second language acquisition by adults tends to lead to grammatical simplification. This theory is built on many anecdotal case studies, including developments in the history of Continental North Germanic associated with contact with Middle Low German. In this paper, we assess the theory by examining two changes in the history of Norwegian: the loss of coda /Cr/ clusters and the loss of prepositional genitives. If the theory is correct, these changes should have been innovated in centers of contact with Middle Low German. We find that both changes in fact spread into southeastern Norwegian from Swedish. Since contact with Low German also took place in Sweden and Denmark, this is consistent with the theory. It opens questions for future research about the role of dialect contact in simplificatory change in North Germanic.